2018
DOI: 10.1002/uog.18923
|View full text |Cite|
|
Sign up to set email alerts
|

Congenital Uterine Malformation by Experts (CUME): better criteria for distinguishing between normal/arcuate and septate uterus?

Abstract: Objectives (CCC, 0.99; 95% CI, was better than both indentation angle (CCC, 0.96; 95% CI, 0.92; 95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
134
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 41 publications
(60 reference statements)
4
134
0
8
Order By: Relevance
“…3D imaging and automatic quantification of a niche with the possibility of detailed offline analysis should be considered in future studies. We acknowledge that the proposed cut‐offs in the VTS niche scoring system are arbitrary, and they should be considered only until proper cut‐offs based on agreement, reliability and diagnostic accuracy become available. Furthermore, the clinical relevance of specific features of a uterine niche and the effectiveness of any intervention should be confirmed by appropriate trials before any changes in clinical practice are considered.…”
Section: Techniquementioning
confidence: 99%
“…3D imaging and automatic quantification of a niche with the possibility of detailed offline analysis should be considered in future studies. We acknowledge that the proposed cut‐offs in the VTS niche scoring system are arbitrary, and they should be considered only until proper cut‐offs based on agreement, reliability and diagnostic accuracy become available. Furthermore, the clinical relevance of specific features of a uterine niche and the effectiveness of any intervention should be confirmed by appropriate trials before any changes in clinical practice are considered.…”
Section: Techniquementioning
confidence: 99%
“…Although the ESHRE/ESGE classification attempted to address all the previous shortcomings, with more objective definitions of CUAs, particularly for septate uterus, it has received criticism, as some authors have observed an increase in the diagnosis of septate uterus compared with former classifications . The Congenital Uterine Malformation Experts (CUME) group has recently criticised ESHRE/ESGE criteria as overestimating and ASRM criteria as underestimating the prevalence of septate uterus, based on a reproducibility and diagnostic accuracy study using 3D ultrasound. The proportion of septate uteri using the ESHRE/ESHE classification was demonstrated to be much higher than using the ASRM criteria (RR 13.9; 95% CI 5.9–32.7, P ≤ 0.01) .…”
Section: Classificationmentioning
confidence: 99%
“…However, these criteria, similarly to those recommended recently by the American Society for Reproductive Medicine (ASRM) and those by the common working group of the European Society of Human Reproduction and Embryology and the European Society for Gynaecological Endoscopy (ESHRE‐ESGE), were derived arbitrarily and without being validated. Now, however, validation of these criteria has been performed, allowing assessment of the results, limitations and implications of this study from a wider perspective.…”
mentioning
confidence: 99%
“…In the Congenital Uterine Malformation by Experts (CUME) study, published in this issue of UOG, the subjective judgments of 15 experts, comprising clinicians, surgeons and sonologists, in distinguishing between septate and normal/arcuate uterus were quantified. The final CUME definitions with the best cut‐offs are a reasonable reference standard for validation of currently used criteria of normal/arcuate and septate uterus.…”
mentioning
confidence: 99%
See 1 more Smart Citation